Evaluating workforce developments to support children of mentally ill parents: implementing new interventions in the adult mental healthcare in Northern Norway - Reedtz, Charlotte; Lauritzen, Camilla; vanDoesum, Karin; Martinussen, Monica (BMJ Open, 2012)
According to new Norwegian laws, mental healthcare for adults are obligated to assess all patients who are parents and to act on their children's needs. This article describes the study protocol of implementing the interventions Family Assessment and Child Talks for children of patients in the adult psychiatry of the University Hospital of Northern Norway. The project is designed to evaluate the process of changes in clinical practice due to the implementation of two interventions. The interventions to be implemented are a standardised Family Assessment Form and the intervention called Child Talks. The family assessment form is an intervention to identify children of mentally ill parents and their needs. The intervention Child Talks is a health-promoting and preventive intervention where the mental health workers talk with the family about the situation of the children and their needs. There are two groups of participants in this study: (1) mental health workers in the clinic (N=220) and (2) patients who are parents (N=200) receiving treatment in the clinic. (1) In the evaluation of clinical practice, the authors use a pre-test, post-test and 1-year follow-up design. At pre-test, the authors evaluate status quo among mental health workers in the clinic regarding knowledge, attitudes, collaborative routines and clinical practice related to families with parental mental illness. After the pre-test is finished, the project move on to implement the interventions Family Assessment Form and Child Talks in the clinic. At post-test and 1-year follow-up, the authors evaluate the impact of implementing the Family Assessment Form in terms of how many children were identified and offered Child Talks in the clinic or referred to other services for additional support. (2) In the evaluation of parents/patients experience with the interventions, the authors use a pre-test post-test design. To identify children of mentally ill patients, the authors collect data on demographical variables for the patient and the child at ...